Kerosene-water counter-current two-phase flow-structures varying flow-orientation in 15 mm diameter duct. (October 2021) - Samal, Kumar; Ghosh, Suman
Abstract: Experimentations are conducted, and kerosene-water counter-current two-phase flow-structure in a duct of 15 mm diameter are identified, categorized, and characterized in five duct-orientations for different combinations of kerosene and water superficial velocities. Some unique counter-current liquid-liquid flow-structures, which have not yet been reported till date, are found through the present experimental investigation. Flow-structures' interfacial distributions and highly time-varying attributes are captured using a high-resolution DSLR camera and a high-speed video camera, respectively, to distinguish and identify them. The subjective descriptions may confuse the observer. Thus, the objective interpretations of the flow-structures are collected as time-series current and voltage signals using a DPT and in-house fabricated conductivity probes, respectively. Statistical analyses of the time-series data are performed, and statistical parameters are extracted using MATLAB coding. The flow-structures are successfully parameterized and characterized in terms of the 'non-parametric probability distribution (NPPD)' plots and those statistical parameters of the objective signatures. These extracted NPPD plots and statistical parameters are found to be very useful for recognizing and distinguishing the individual flow-structures. Graphical abstract: Image 1 Highlights: Novel liquid-liquid CCTPF-structures in a 15 mm ID tube for 5 flow-orientations are experimentally identified. High-resolution images of the developed complex flow-structures are recorded using a DSLR camera. Flow-structures' rapidly time-varying attributes are captured by high-speed videography using a high-speed camera. Flow-structures' objective interpretations are collected using DPT and in-house fabricated CP. Flow-regimes are expressed using the NPPD plots and statistical parameters of the objective interpretations.